Inferior Glenohumeral Ligament (IGHL) Injuries: A Case Series of Magnetic Resonance (MR) Imaging Findings and Arthroscopic Correlation - Glass, Michael; Behzadpour, Vafa; Peterson, Jessica; Clark, Lauren; Bell-Glenn, Shelby; Ni, Yonghui; Walter, Carissa; Beteselassie, Nebiyu (Kansas Journal of Medicine, 2020)
Introduction. The inferior glenohumeral ligament (IGHL) complex commonly is assessed by both magnetic resonance imaging (MRI) and magnetic resonance (MR) arthrogram. Our study compared the accuracy of MR arthrogram compared to MRI using arthroscopic correlation as the gold standard. Methods. A retrospective review of cases reporting an IGHL injury was performed. Seventy-seven cases met inclusion criteria, while five had arthroscopic reports that directly confirmed or refuted the presence of IGHL injury. Two arthroscopic reports confirmed concordant IGHL injuries, while three arthroscopic reports mentioned discordant findings compared to MR. All three discordant cases involved MR arthrogram. Findings included soft tissue edema, fraying of the axillary pouch fibers, and cortical irregularity of the humeral neck. Of the two concordant cases, one was diagnosed by MRI, revealing an avulsion of the anterior band, while the second was diagnosed by MR arthrogram showing ill-defined anterior band fibers. Many cases involved rotator cuff or labral tears, which may have been the focus of care for providers, given their importance for shoulder stability. Additionally, a lack of diagnostic confidence in MR reports may have influenced surgeons in the degree to which they assessed the IGHL complex during arthroscopy. Conclusion. Radiologists seemed more likely to make note of IGHL injuries when MR arthrograms were performed; meanwhile, all three discordant cases involved MR arthrogram reads. Therefore, additional larger studies are needed with arthroscopic correlation to elucidate MR findings that confidently suggest injury to the IGHL complex, to avoid false positive radiology reports.